2015
DOI: 10.1371/journal.pone.0140323
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Preoperative Thrombin Time in Patients with Esophageal Squamous Cell Carcinoma following Surgical Resection

Abstract: BackgroundNoninvasive tools for the prognosis of ESCC are urgently needed. To this end, serum coagulation tests have been researched in some cancers, but the prognostic value of the TT in ESCC has not been described.MethodsThe levels of pre-treatment serum coagulation markers (including the PT, APTT, PTA, INR, fibrinogen level, TT and PLT) were retrospectively analyzed in 204 patients with ESCC who underwent surgical resection at our department and in 200 healthy controls, and the two groups were compared. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Wakatsuki et al 10 and Takeuchi et al 11 demonstrated that plasma Fib was a useful independent predictive indicator for prognosis in ESCC. Conversely, Li et al 12 revealed that Fib was not associated with the OS of ESCC. Recently, two meta-analyses revealed that plasma Fib was a prognostic indicator in patients with EC 13,14 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Wakatsuki et al 10 and Takeuchi et al 11 demonstrated that plasma Fib was a useful independent predictive indicator for prognosis in ESCC. Conversely, Li et al 12 revealed that Fib was not associated with the OS of ESCC. Recently, two meta-analyses revealed that plasma Fib was a prognostic indicator in patients with EC 13,14 .…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that fibrinogen (Fib), a major protein in the blood clotting process, is associated with cancer 6 . Although recent studies have reported that plasma Fib was related to cancer progression and prognosis in various cancers [7][8][9] , the role of plasma Fib in EC remains controversial [10][11][12] . Recently, two metaanalyses revealed that plasma Fib was a prognostic indicator in patients with EC 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…And the associations between coagulation system and cancer have been frequently studied 16 . First of all, many studies have demonstrated that coagulation system has an effect on the solid tumors, such as ESCC 10 , penile cancer 17 , HCC 18 , lung cancer 11 and so on. Secondly, hematological system diseases have been reported related to this 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, abnormal coagulation parameters that represent hemostatic and fibrinolytic systems have been associated with tumor progression and dissemination, which could decrease overall survival (OS) of tumors 9 . In our previous study, the decreased pre-treatment thrombin time (TT) was reported to be associated with the shorter ESCC survival 10 . Research was conducted by Tas et al 11 , who reported the prognostic values of the prothrombin time (PT) and international normalized ratio (INR) in lung cancer.…”
Section: Introductionmentioning
confidence: 98%
“…However, the sensitivity and specificity are not sufficient or reliable. Furthermore, correlations between ESCC survival and thrombin time (TT) [ 7 ] or apolipoprotein A1 (Apo-A1) [ 8 ] have been reported in our previous study. Thus, in order to improve the posttreatment survival of patients, identification of more effective and accurate biomarker of ESCC is a necessity.…”
Section: Introductionmentioning
confidence: 99%